Utilisation of evidence from Thailand's National Health Examination Survey in policy development: finding the weakest link - Sripen Tantivess; Jomkwan Yothasamut; Wilailak Saengsri (BMC, 2019)
Abstract Background Health surveillance and survey data are helpful in evidence-informed policy decisions. This study is part of an evaluation of the National Health Examination Survey (NHES) programme in Thailand. This paper focuses on the obstacles in the translation of survey information into policies at a national level. Methods In-depth interviews with relevant individuals and representatives of institutes were carried out for the data collection. A total of 26 focal informants included executives and staff of NHES funders, government health agencies, civil society organisations, health experts, NHES programme managers and researchers in the survey network. Results Utilisation of NHES data in policy-making is limited for many reasons. Despite the potential users' positive views on the technical integrity of experts and practitioners involved in the NHES, the strength of employing health examinations in the data collection is not well recognised. Meanwhile, alternative health surveillance platforms that offer similar information on a shorter timescale are preferable in policy monitoring and evaluation. In sum, the lack of governance of Thailand's health surveillance system is identified as a key element hindering the translation of health surveys, including the NHES, into policies. Conclusion Despite an adequate capacity to conduct population health surveys, the lack of governance structure and function has resulted in a fragmented health monitoring system. Large and small survey projects are conducted and funded by different institutes without common policy direction and alignment mechanisms for prioritising survey topics, collective planning and capacity-building programmes for survey practitioners and users. Lessons drawn from Thailand's NHES can be helpful for policy-makers in other low- and middle-income countries, as effective governance for evidence generation and utilisation is necessary in all contexts, regardless of income level and available resources.